Wellbeing, freedom and social justice the capability approach re-examined - Robeyns, Ingrid; Open Book Publishers (Open Book Publishers, 2017)
"How do we evaluate ambiguous concepts such as wellbeing, freedom, and social justice? How do we develop policies that offer everyone the best chance to achieve what they want from life? The capability approach, a theoretical framework pioneered by the philosopher and economist Amartya Sen in the 1980s, has become an increasingly influential way to think about these issues. Wellbeing, Freedom and Social Justice: The Capability Approach Re-Examined is both an introduction to the capability approach and a thorough evaluation of the challenges and disputes that have engrossed the scholars who have developed it. Ingrid Robeyns offers her own illuminating and rigorously interdisciplinary interpretation, arguing that by appreciating the distinction between the general capability approach and more specific capability theories or applications we can create a powerful and flexible tool for use in a variety of academic disciplines and fields of policymaking. This book provides an original and comprehensive account that will appeal to scholars of the capability approach, new readers looking for an interdisciplinary introduction, and those interested in theories of justice, human rights, basic needs, and the human development approach."--Publisher's website.
Acknowledgements -- 1. Introduction ;1.1 Why the capability approach?;1.2 The worries of the sceptics ;1.3 A yardstick for the evaluation of prosperity and progress ; 1.4 Scope and development of the capability approach ;1.5 A guide for the reader -- 2. Core Ideas and the Framework ; 2.1 Introduction ; 2.2 A preliminary definition of the capability approach ; 2.3 The capability approach versus capability theories ;2.4 The many modes of capability analysis ; 2.5 The modular view of the capability approach ; 2.6 The A-module: the non-optional core of all capability theories ; 2.6.1 A1: Functionings and capabilities ; 2.6.2 A2: Functionings and capabilities are value-neutral categories ; 2.6.3 A3: Conversion factors ; 2.6.4 A4: The means-ends distinction ; 2.6.5 A5: Functionings and capabilities as the evaluative space ; 2.6.6 A6: Other dimensions of ultimate value ; 2.6.7 A7: Value pluralism ; 2.6.8 A8: The principle of each person as an end ; 2.7 The B-modules: non-optional modules with optional content ; 2.7.1 B1: The purpose of the capability theory ; 2.7.2 B2: The selection of dimensions ; 2.7.3 B3: Human diversity ; 2.7.4 B4: Agency ; 2.7.5 B5: Structural constraints ; 2.7.6 B6: The choice between functionings, capabilities, or both ; 2.7.7 B7: Meta-theoretical commitments ; 2.8 The C-modules: contingent modules ; 2.8.1 C1: Additional ontological and explanatory theories ; 2.8.2 C2: Weighing dimensions ; 2.8.3 C3: Methods for empirical analysis ; 2.8.4 C4: Additional normative principles and concerns ; 2.9 The modular view of the capability account: a summary ; 2.10 Hybrid theories ; 2.11 The relevance and implications of the modular view ; 2.12 A visualisation of the core conceptual elements ; 2.13 The narrow and broad uses of the capability approach ; 2.14 Conclusion -- 3. Clarifications ; 3.1 Introduction ; 3.2 Refining the notions of 'capability' and 'functioning' ; 3.2.1 Capability as an opportunity versus capability as an opportunity set ; 3.2.2 Nussbaum's terminology ; 3.2.3 What are 'basic capabilities'? ; 3.2.4 Conceptual and terminological refinements ; 3.3 Are capabilities freedoms, and if so, which ones? ; 3.3.1 Capabilities as positive freedoms? ; 3.3.2 Capabilities as opportunity or option freedoms? ; 3.3.3 Are capabilities best understood as freedoms? ; 3.4 Functionings or capabilities? ; 3.5 Human diversity in the capability approach ; 3.6 Collective capabilities ; 3.7 Which notion of wellbeing is used in the capability approach? ; 3.7.1 The aim and context of accounts of wellbeing ; 3.7.2 The standard taxonomy of philosophical wellbeing accounts ; 3.7.3 The accounts of wellbeing in the capability approach ; 3.8 Happiness and the capability approach ; 3.8.1 What is the happiness approach? ; 3.8.2 The ontological objection ; 3.8.3 Mental adaptation and social comparisons ; 3.8.4 Comparing groups ; 3.8.5 Macro analysis ; 3.8.6 The place of happiness in the capability approach ; 3.9 The capability approach and adaptive preferences ; 3.10 Can the capability approach be an explanatory theory? ; 3.11 A suitable theory for all normative questions? ; 3.12 The role of resources in the capability approach ; 3.13 The capability approach and theories of justice ; 3.13.1 A brief description of the literature on theories of justice ; 3.13.2 What do we need for a capability theory of justice? ; 3.13.3 From theories of justice to just practices and policies ; 3.14 Capabilities and human rights ; 3.14.1 What are human rights? ; 3.14.2 The interdisciplinary scholarship on human rights ; 3.14.3 Why a capability-based account of human rights? ; 3.14.4 Are capabilities sufficient to construct a theory of human rights? ; 3.14.5 The disadvantages ; 3.15 Conclusion -- 4. Critiques and Debates ; 4.1 Introduction ; 4.2 Is everything that's called a capability genuinely a capability? ; 4.3 Should we commit to a specific list of capabilities? ; 4.4 Why not use the notion of needs? ; 4.5 Does the capability approach only address the government? ; 4.6 Is the capability approach too individualistic? ; 4.6.1 Different forms of individualism ; 4.6.2 Does the capability approach pay sufficient attention to groups? ; 4.6.3 Social structures, norms and institutions in the capability approach ; 4.7 What about power and political economy? ; 4.7.1 Which account of power and choice? ; 4.7.2 Should we prioritise analysing the political economy? ; 4.8 Is the capability approach a liberal theory? ; 4.9 Why 'human development' is not the same idea ; 4.10 Can the capability approach change welfare economics? ; 4.10.1 Welfare economics and the economics discipline ; 4.10.2 Non-welfarism ; 4.10.3 Empirical possibilities and challenges ; 4.10.4 Towards a heterodox capabilitarian welfare economics? ; 4.11 Taking stock -- 5. Which Future for the Capability Approach? -- References -- Index.
Available through Open Book Publishers.
Includes bibliography (pages 217-249) and index.
Mode of access: World Wide Web.
Keywords: Basic needs; Economic development; Social justice